Breastfeeding Practice and Awareness Among Women of Child Bearing Age in Abia State Nigeria - Udujih, Godwin Obinna; Elekanachi, Harriet; Udujih, Helen Ifeoma; Iwuala, Chimezie Christian (British Journal of Healthcare and Medical Research, 2023)
Breast feeding practice and awareness among women of child bearing age in Abia State Nigeria were assessed using a structured questionnaire in a clustered random sampling. Out of the 392 women who participated, the demographic data showed an average of 32 years with majority (55.2%) of them were married. The highest educational attainment for most of the women was secondary education (40.0%) while the average number of child per woman was four. Most were self-employed with an average income of between 20,000 -50,000 naira per month. The study further revealed that majority (85.5%) of the women were aware of exclusive breastfeeding with health workers (58.5%) and family members (27.0%) being the major sources of awareness. At the time of survey, only 28.6% of the women were breast feeding and the average of babies being breastfed was found to be 3weeks and 3months old. Major constraints to breastfeeding practice was lack of medical support (35%), return to school (41.8%) and no funding (42.0%). The misconceptions towards breastfeeding were fear of interactions with harmful medications (5.8%), breast fed babies are smaller that formula babies (9.7%), certain foods consumed by mother will harm baby (19.0%). Awareness and practice of exclusive breast feeding could be improved by encouraging social and financial support systems through targeted projects of the government and non-profit organizations. It is also necessary to extend awareness programs to family members and the society at large.